2015
DOI: 10.4238/2015.december.29.4
|View full text |Cite
|
Sign up to set email alerts
|

Association of TNF-α G308A gene polymorphism in essential hypertensive patients without type 2 diabetes mellitus

Abstract: ABSTRACT. This study aims to investigate the effects of tumor necrosis factor alpha (TNF-α) G308A gene polymorphism on essential hypertension (EHT) with or without type 2 diabetes mellitus (T2DM). The project was conducted on buccal epithelial and blood cells for case and control patients, respectively. Epithelial cells were obtained from the inner part of the cheeks. Techniques including DNA extraction, polymerase chain reaction (PCR), and restriction fragment length polymorphism (RFLP) were utilized to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 15 publications
0
6
0
5
Order By: Relevance
“…30,31 Increasing numbers of scholars are exploring scholars the relationship between TNF-a -308G/A polymorphism and EH, but the conclusions are not consistent. [18][19][20][21][22][23][24][25][26] A single study may not draw a comprehensive and reliable conclusion due to the low effectiveness of the tests used. In addition, because of the different frequencies (TNF-a -308G/A) of the different regions and ethnic groups, the extrapolation of the foreign research is limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30,31 Increasing numbers of scholars are exploring scholars the relationship between TNF-a -308G/A polymorphism and EH, but the conclusions are not consistent. [18][19][20][21][22][23][24][25][26] A single study may not draw a comprehensive and reliable conclusion due to the low effectiveness of the tests used. In addition, because of the different frequencies (TNF-a -308G/A) of the different regions and ethnic groups, the extrapolation of the foreign research is limited.…”
Section: Discussionmentioning
confidence: 99%
“…17 Finally, a total of nine casecontrol studies were identified, including 1437 cases and 1487 controls. [18][19][20][21][22][23][24][25][26] These nine studies encompassed one Caucasian and eight Asian studies. The characteristics of the selected studies and the numbers of subjects are shown in Table 1.…”
Section: Study Selection and Subject Characteristicsmentioning
confidence: 99%
“…is associated with higher plasma TNF-alpha levels and this polymorphism is a predisposition of OSA (Sun et al, 2015) and hypertension (Ghodsian et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Polymorphisms in the leptin receptor (LTPR) gene were significantly associated with the risk of hypertension (Lian, Tang, Xie, & Chen, ), T2DM (Su et al, ) and OSA (Xu, Liu, Li, & Liu, ). Finally, tumor necrosis factor‐alpha (TNF‐alpha) G308A is associated with higher plasma TNF‐alpha levels and this polymorphism is a predisposition of OSA (Sun et al, ) and hypertension (Ghodsian et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes mellitus (DM) is an endocrinal and metabolic disease featuring high blood glucose (de Azevêdo Silva et al, 2015;Ghodsian et al, 2015). Following cardiovascular disease and cancer, DM is the third serious chronic, non-infectious disease threatening human health.…”
Section: Introductionmentioning
confidence: 99%